Historical trends of organochlorine pesticides in an Alpine glacier - Villa, S; Vighi, M; Maggi, V; Finizio, A; Bolzacchini, E (KLUWER ACADEMIC PUBL, 2003)
The significance of persistent organic pollutants, such as organochlorine compounds, as global contaminants in cold regions has been recognised for a long time. In particular, there is a growing interest on the role of high mountains as 'cold condensers' for these chemicals. In this paper, for the first time, organochlorine pesticides (DDTs, HCHs, HCB) are analysed in an ice core sampled on a 'cold' glacier in the Alps. Several methods were applied to achieve accurate dating of the core layers. Historical trends of organochlorine pesticides from the 1950s up to the year 2000 are reconstructed, showing, for each individual chemical, the influence of long range transport, as well as of local transport patterns. The role of mountain glaciers as natural archives for studying the local and global transport of persistent organic pollutants is highlighted, though results can be biased by volatilisation losses.